Career Adaptability Across Southeast Asia: A Systematic Review - Divyashine, Asok Kumar; Lau, Poh Li; Chua, Kah Heng; Voon, Siok Ping; Lo, Yueh Yea (SAGE Publications Inc., 2024)
Southeast Asia has recently seen a number of developments and transformations that requires one to adjust to as the region’s skill requirements are evolving. For some these new changes brings new opportunities, however, for some greater levels of career adaptability is need to manage these new developments and transformations. The necessity of systematically reviewing articles on career adaptability in Southeast Asian nations is made apparent by this particular instance. A systematic review of career adaptability in Southeast Asia was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. About 22 eligible studies were identified. The findings indicated that the most prevalent groups in career adaptability studies were students, followed by working adults. Antecedents such as role modeling and cultural intelligence were identified. Four categories of predictors were identified such as personal, educational, career behavior, and environmental factor. Two categories were identified for the outcomes of career adaptability, namely, personal and career outcomes. Findings revealed that career adaptability offers several beneficial outcomes such as improved employability skills and life satisfaction. Discussion includes conditions faced in Southeast Asian countries and cultural differences. The dearth of studies within multicultural settings calls for further research in exploring career adaptability, as this broaden cultural understanding and awareness of educational and career behaviors pertaining to one’s career adaptability. This study offers important practical implications and recommendations for career counseling practices and policymakers in Southeast Asia that would potentially benefit students and working adults.